A virtual instrument for quantitative assessment of pitting corrosion. Issue 5 (19th August 2014) - Ramos, Rogelio; Valdez, Benjamin; Zlatev, Roumen; Schorr, Michael; Carrillo, Mónica; Stoytcheva, Margarita; Garcia, Ramses; Martinez, Miguel
Abstract : Purpose: The purpose of this paper is to develop a digital instrument for the quantitative evaluation of pitting corrosion in metals. Design/methodology/approach: This investigation comprises two central parts: research, testing and monitoring of the formation of pitting by conventional methods applying ASTM standards and the development of a virtual instrument based on the LabVIEW 2010 platform. Findings: The methodology used was suitable for the analysis of pitting in carbon steel and aluminum alloy UNS A96061, used in aerospace industry. Practical implications: This technique allows to localize, measure and quantify pits on metallic surfaces, for corrosion control in the environment and industry. Originality/value: This combination of conventional and digital methods will assist in corrosion control of pitting in industrial equipment.